2021
DOI: 10.29333/ejgm/10831
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant and Newborn Health in COVID-19 Pandemic: Knowledge level, Attitude and Perspective of Obstetricians & Gynecologists and Pediatricians in Turkey (A Survey-based Study)

Abstract: The COVID-19 is a rapidly ongoing pandemic. 368.513 cases and 10.027 fatalities have been reported in Turkey up to this day. Pregnant women and newborns constitute a special patient group in this disease. In our study, we aimed to measure the knowledge level, attitude to protective measures, perspective of education and medicolegal issues of obstetricians -gynecologists (OB-GYN) and pediatricians on pregnant and newborn health about COVID-19. Material-Methods:A cross-sectional, online-survey consisted of 22 qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Despite reports that the disease generally has a milder course in children and mortality is rare, it has been reported that the risk of morbidity and mortality of COVID-19 can be high in children with underlying disorders such as pulmonary dysfunction or immune suppression [6,7]. Previous studies in several countries have reported that healthy children with positive test results for COVID-19 have a mild course of disease and more often play a major role in the spread of the disease as asymptomatic carriers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite reports that the disease generally has a milder course in children and mortality is rare, it has been reported that the risk of morbidity and mortality of COVID-19 can be high in children with underlying disorders such as pulmonary dysfunction or immune suppression [6,7]. Previous studies in several countries have reported that healthy children with positive test results for COVID-19 have a mild course of disease and more often play a major role in the spread of the disease as asymptomatic carriers [8][9][10].…”
Section: Introductionmentioning
confidence: 99%